Composition, structural configuration, and antigenicity of Atlantic cod (Gadus morhua) tropomyosin. (15th January 2023) - Zhao, Yaqi; Jiang, Xingyi; Tang, Chunya; Rao, Qinchun
Highlights: CTM is purified by isoelectric precipitation and anion-exchange chromatography. CTM retains solubility, molecular integrity, and antigenicity after heat treatment. Disulfide-reduced CTM dimers are the vast majority under native condition. CTM contains tetramers and three monomeric α isoforms under non-reducing condition. β-Mercaptoethanol can dissociate disulfide-induced CTM tetramers and conjugates. Abstract: Tropomyosin, a myofibrillar muscle protein, has been recognized as a finfish allergen. In this study, tropomyosin from Atlantic cod fillets ( Gadus morhua, CTM ) was purified using a two-step purification strategy (isoelectric precipitation and anion-exchange chromatography). CTM structural configuration in two sample matrices (impure and pure) were elaborated using different polyacrylamide gel electrophoresis (native, non-reducing, and reducing PAGE). Their corresponding immunoblots were conducted to investigate CTM antigenicity under three conditions. Overall, CTM retained solubility, integrity, and antigenicity after heat treatment. Three CTM monomeric α-type isoforms (33 kDa) were identified using two-dimensional PAGE. Under native condition, the vast majority of CTM existed in the disulfide-reduced dimeric form (66 kDa). Under non-reducing condition, sodium dodecyl sulfate (anionic surfactant) broke CTM dimers, leaving monomers and disulfide-induced tetramers. Under reducing condition, β-mercaptoethanol (thiol reducing agent) dissociated disulfide-linked CTM tetramers (132 kDa) into monomers (33 kDa). CTM retained antigenicity regardless of structural configuration under different conditions.